A Research On Microstrip Array Antenna At 850 MHz Fre-quency - Rizky Andromedha Persia; Beni Satria; Dicky Lesmana (Sean Institute, 2024)
A Microstrip antenna is an antenna that has advantages in physical form, namely an antenna with a small shape so that it is easy to integrate. In addition to the small form of this antenna, it also has disadvantages such as narrow bandwidth and low gain. One of the solutions is that microstrip antennas can be designed using array techniques. The array technique in the design of the microstrip antenna is designed for the frequency of 850 MHz. This frequency is commonly used by communications service providers for LTE purposes. The material used is PCB epoxy (FR4) double layer with a thickness of 1.3 mm and a dielectric constant of 4.7. The shape of the patch made is a rectangle and a circle. The microstrip antenna was tested to obtain the value of the resonant frequency, VSWR and radiation pattern which then the results were compared with the simulation results using the IE3D microstrip simulator software. In the test, the results were obtained for a rectangular microstrip array antenna.